Implementing geometry-related environmental indicators in a 3d-gis - Souza, Léa Cristina Lucas (2003)
This paper highlights the suitability of applying a 3D GIS to analyze geometry-related environmental indicators. The work starts with a discussion and application of a tool developed to identify sky view factors. Called 3DSKYVIEW extension, this tool was produced as part of a research cooperation effort established between Brazil and Portugal to identify common urban environmental indicators for their medium sized cities. The sky view factor (SVF) is a parameter used to characterize radiation properties on urban areas and to express the relationship between the visible area of the sky and the portion of the sky covered by buildings viewed from a specific point of observation. The 3DSKYVIEW extension is an algorithm developed by applying the software ArcView GIS1 and its 3D Analyst extension, allowing an automatic delineation of the visible sky and obstructions. The implementation of this tool in a 3D GIS is useful because it allows straight and quick urban geometry analysis from several points of observation. Furthermore, it can be seen as a single environmental indicator of thermal, lighting and acoustical performance of urban areas, as suggested by the exploratory study conducted in a medium-sized Brazilian city and summarized in this paper.